Management in Marketing Communications (IntechOpen, 2025)
This book provides a comprehensive overview of the essential topics in the field of management in marketing communication. These substantial topics are examined and addressed by scholars from the marketing and management discipline. Beginning with the role of culture as a crucial element in marketing communication, the book delves into various matters within the scope of marketing communication. Consequently, social media and its significance in modern marketing strategies are examined together with the topic of transition from offline to online marketing, emphasizing the impact of accelerated digitalization and its onset during the third decade of the twenty-first century. Furthermore, the book discusses the rapid digital transformation stimulated by the COVID-19 pandemic and thus creates room for further exploration and research. Throughout the book, the evolving dynamics of marketing communication in a digitalized world are examined, providing a resource base for scholars conducting research in the context of modern marketing management.